Motivasi Kerja Dosen PTN Ditinjau Dari Karakteristik lndividu (Analisis Teori Motivasi Maslow) - Murni, Wahid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
This research aims to describe work motivation of lecturers in Malang Universities which is measured individually. Using descriptive quantitative approach, the research gathers the data in the form of scores by using/giving questionnaires to the lectures, all of which are government employees, as data sources. Then the data will be analysed by quantifyng every answer is referred to a given table. The result of research reveals that most respondents consider highly important all kinds of following needs, such as (1) physiological need, (2) self security need, (3) social need, (4) self respect need, and (5) self actualizing needs should be fulfilled simultaneously. The findings do not support Maslow s theory that people will be motivated if their needs are fulfilled.